Performing Utopia? The Contestation of Dystopian Space in Cecelia Ahern's Flawed-Series - Schneider, Julia Christina (Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre)

Investigation into Target Speaking Rate Adaptation for Voice Conversion - Kuhlmann, Michael; Seebauer, Fritz; Ebbers, Janek; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2022)

Schorsch Kamerun: „Extra Vages machen wir aus tiefer Überzeugung“. - Jacke, Christoph (Kaput. Magazin für Insolvenz & Pop.)

Forward & Rewind: Retromania in Music Documentary. - Jacke, Christoph; Reynolds, Simon (Jugend, Musik und Film.)

Ein kommentierter Tagungsbericht zur 4. Werkstatt Unterrichtsfach Pädagogik Ostwestfalen-Lippe (WUPO) - Engemann, Mario (Zeitschrift PädagogikUNTERRICHT)

The Greatest Advantage of Polytheism: Monotheism and Normalization through Truth - Corall, Niklas (Nietzsche's Gods)

What kind of leader am I? An exploration of professionals' leader identity construal - Rehbock, Stephanie K.; Hubner-Benz, Sylvia; Knipfer, Kristin; Peus, Claudia V. (Applied Psychology)
Although the leadership literature has emphasized the importance of leader identity for leader behaviors and leader effectiveness, little is known about whether and how professionals, who are experts in their field and hold a formal leader role, construe a leader identity. To expand our understanding of leader identity construal, we explored how professors in German research universities interpreted their formal leader role and whether and how they saw themselves as leaders. Based on findings from an inductive interview study, we contribute to the literature in three ways: First, our findings imply that patterns of professional identity and leader identity dimensions likely predict when a leader role is rejected , accommodated , incorporated , or emphasized . Second, we explain why professionals with a formal leader role see themselves primarily as specialists , mentors , managers , or shapers . Third, we extend previous notions of the leader identity concept by elaborating on its dimensions. Our findings have practical implications on an individual and organizational level, and may help design more effective leadership development programs.
Keywords: Applied Psychology; Arts and Humanities (miscellaneous); Developmental and Educational Psychology

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Far-field Calculation from magnetic Huygens Box Data using the Boundary Element Method - Marschalt, Christoph; Schroder, Dominik; Lange, Sven; Hilleringmann, Ulrich; Hedayat, Christian; Kuhn, Harald; Sievers, Denis; Förstner, Jens (2022 Smart Systems Integration (SSI))
In this publication a novel method for far-field prediction from magnetic Huygens box data based on the boundary element method (BEM) is presented. Two examples are considered for the validation of this method. The first example represents an electric dipole so that the obtained calculations can be compared to an analytical solution. As a second example, a printed circuit board is considered and the calculated far-field is compared to a fullwave simulation. In both cases, the calculations for different field integral equations are under comparison, and the results indicate that the presented method performs very well with a combined field integral equation, for the specified problem, when only magnetic Huygens box data is given.
Keywords: Near-Field Scanning; Huygens Box; Boundary Element Method; Method of Moments; tet_topic_hf

Professionalisierung von Lehramtsstudierenden für sprachbildenden Fachunterricht im Berufsfeld Ernährung und Hauswirtschaft - Dehn, Freya; Meyer, Anja; Niederhaus, Constanze; Schlegel-Matthies, Kirsten (HiBiFo – Haushalt in Bildung & Forschung)
Aufgrund der heterogenen Schülerschaft im Berufsfeld Ernährung und Hauswirtschaft müssen Studierende für sprachbildenden Fachunterricht professionalisiert werden. Aufbauend auf einer theoretischen Fundierung werden konkrete Umsetzungsbeispiele anhand von drei exemplarischen Online-Modulen für den Ausbildungsberuf Hotelfachfrau/-mann vorgestellt.

Prospective Teachers’ Diagnostic Thinking on Students’ Understanding of Multi-Digit Multiplication: A Content-Related Analysis on Unpacking of Knowledge Elements - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik)
Abstract Teachers’ in-depth diagnostic thinking has been shown to be crucial for student-centered teaching as they need to perceive and interpret students’ understanding for well-informed decision-making on adaptive teaching practices. The paper presents a content-related approach to analyzing diagnostic thinking processes with respect to the mathematical knowledge elements that prospective teachers identify as students’ resources and obstacles. Prospective teachers’ challenge is that some relevant knowledge elements first have to be unpacked, because compact concepts (such as the place value concept) or procedures (such as for multi-digit multiplication) comprise several smaller knowledge elements (such as the positional property) that have to be made explicit for students to foster their learning processes adequately. Our study examines what knowledge elements prospective teachers perceive and interpret in a transcript vignettes on multi-digit multiplication (of decimal and natural numbers) and its underlying basic arithmetic concepts (place value understanding and meaning of multiplication) in written diagnostic judgments on students’ resources and obstacles ( N = 196). A comparative design within the vignette is used to investigate how far the process of perceiving can be supported by thematic cues. The analysis reveals that those knowledge elements cued in the vignette by being already unpacked and explicitly addressed are perceived and interpreted more often (but with lower correctness) than those that are uncued and therefore have to be unpacked by the prospective teachers themselves. This confirms the need to prepare prospective teachers for unpacking mathematical concepts themselves.
Keywords: Education; General Mathematics

Prospective Teachers‘ Competence of Fostering Students’ Understanding in Script Writing Task - Dröse, Jennifer; Wessel, Lena (Proceedings of the 45th Conference of the International Group for the Psychology of Mathematics Education. PME)

Batch Constrained Bayesian Optimization for UltrasonicWire Bonding Feed-forward Control Design - Hesse, Michael; Hunstig, Matthias; Timmermann, Julia; Trächtler, Ansgar (Proceedings of the 11th International Conference on Pattern Recognition Applications and Methods (ICPRAM))
Ultrasonic wire bonding is a solid-state joining process used to form electrical interconnections in micro and power electronics and batteries. A high frequency oscillation causes a metallurgical bond deformation in the contact area. Due to the numerous physical influencing factors, it is very difficult to accurately capture this process in a model. Therefore, our goal is to determine a suitable feed-forward control strategy for the bonding process even without detailed model knowledge. We propose the use of batch constrained Bayesian optimization for the control design. Hence, Bayesian optimization is precisely adapted to the application of bonding: the constraint is used to check one quality feature of the process and the use of batches leads to more efficient experiments. Our approach is suitable to determine a feed-forward control for the bonding process that provides very high quality bonds without using a physical model. We also show that the quality of the Bayesian optimization based control outperforms random search as well as manual search by a user. Using a simple prior knowledge model derived from data further improves the quality of the connection. The Bayesian optimization approach offers the possibility to perform a sensitivity analysis of the control parameters, which allows to evaluate the influence of each control parameter on the bond quality. In summary, Bayesian optimization applied to the bonding process provides an excellent opportunity to develop a feedforward control without full modeling of the underlying physical processes.
Keywords: Bayesian optimization; Wire bonding; Feed-forward control; model-free design

Elektrooptischer Mischer - Kruse, Stephan; Scheytt, J. Christoph

Exploring the customer journey of voice commerce: A research agenda - Böhm, Eva; Eggert, A.; Garnefeld, I.; Holzmüller, H.; Schaefers, T; Steinhoff, Lena; Woisetschläger, D. (Journal of Service Management)

Effective vocabulary learning apps: what should they look like? An evaluation with a particular view to German language acquisition - Lentfort, Theresa; Künzl-Snodgrass, Annemarie; de Vincent-Humphreys, Maren (Ab Initio Language Teaching in British Higher Education. The Case of German)

Lil Miquela in the Folds of Fashion: (Ad-)Dressing Virtual Influencers - Brachtendorf, Charlotte (Fashion, Style & Popular Culture 9)

Materialitäten virtueller Mode: das Fallbeispiel The Fabricant (together with Helga Behrmann and Judith Brachem), - Brachtendorf, Charlotte

Mental Rotation of Tactic Board Instructions in Basketball: Domain-Specific Expertise Improves On-Court Performance - Krause, Daniel; Weigelt, Matthias (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

GDSU-Journal

Threshold photoelectron spectroscopy of trimethylborane and its pyrolysis products - Schleier, Domenik; Gerlach, Marius; Schaffner, Dorothee; Mukhopadhyay, Deb Pratim; Hemberger, Patrick; Fischer, Ingo (Physical Chemistry Chemical Physics)
A new decomposition mechanism for trimethylborane at high temperatures has been discovered.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Gemeinsam mehrgleisig an einem Strang. Begleitforschung in InnoVET als Grundlage für nachhaltige Translationsprozesse bei Programmdurchführungen - Ertl, Hubert; Peitz, Nina-Madeleine (Zeitschrift für Berufs- und Wirtschaftspädagogik)

Informed vs. Blind Beamforming in Ad-Hoc Acoustic Sensor Networks for Meeting Transcription - Gburrek, Tobias; Schmalenstroeer, Joerg; Heitkaemper, Jens; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))

Oratorium und Nation (1914–1945) - Höink, Dominik
Das Oratorium kann als wichtige Gattung für die Analyse des Zusammenspiels von Religion und Politik im Medium der Musik gelten. Die Studie wendet sich dem Verhältnis dieser religiösen Musikform zum deutschen Nationalismus vom Beginn des Ersten bis zum Ende des Zweiten Weltkriegs zu. Im Fokus stehen verschiedene Weisen der Instrumentalisierung von Musik, etwa zur ‚Heldenehrung‘, zur Bildung einer ‚vorgestellten Gemeinschaft‘ oder zur Gewinnung der Arbeiterschaft. Bei der Analyse der Politisierung des Oratoriums sind vier Beobachtungsperspektiven leitend: Konfession, Säkularisierung, Erinnerungskultur und Vergemeinschaftung. Entsprechend liegt der Schwerpunkt der Studie auf der Analyse der sozialgeschichtlichen Funktion der Gattung. Daneben jedoch werden – in Form von Fallstudien zu bisher unerforschten Werken – auch musikalische Detailanalysen durchgeführt, die das in der jeweiligen Komposition realisierte Verhältnis von religiösen und nationalistischen Elementen offenlegen.

A Meeting Transcription System for an Ad-Hoc Acoustic Sensor Network - Gburrek, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Cord-Landwehr, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold

Jeanne d’Arc in Bildern vom 15. Jahrhundert bis zur Gegenwart - Moritz, Tilman (Katechetische Blätter)

Threshold Independent Evaluation of Sound Event Detection Scores - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
Performing an adequate evaluation of sound event detection (SED) systems is far from trivial and is still subject to ongoing research. The recently proposed polyphonic sound detection (PSD)-receiver operating characteristic (ROC) and PSD score (PSDS) make an important step into the direction of an evaluation of SED systems which is independent from a certain decision threshold. This allows to obtain a more complete picture of the overall system behavior which is less biased by threshold tuning. Yet, the PSD-ROC is currently only approximated using a finite set of thresholds. The choice of the thresholds used in approximation, however, can have a severe impact on the resulting PSDS. In this paper we propose a method which allows for computing system performance on an evaluation set for all possible thresholds jointly, enabling accurate computation not only of the PSD-ROC and PSDS but also of other collar-based and intersection-based performance curves. It further allows to select the threshold which best fulfills the requirements of a given application. Source code is publicly available in our SED evaluation package sed_scores_eval.

"They’re not that hard to mitigate": What Cryptographic Library Developers Think About Timing Attacks - Jancar, Jan; Fourné, Marcel; Braga, Daniel De Almeida; Sabt, Mohamed; Schwabe, Peter; Barthe, Gilles; Fouque, Pierre-Alain; Acar, Yasemin (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

Committed to Trust: A Qualitative Study on Security & Trust in Open Source Software Projects - Wermke, Dominik; Wöhler, Noah; Klemmer, Jan H.; Fourné, Marcel; Acar, Yasemin; Fahl, Sascha (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

"Desperate Times Call for Desperate Measures": User Concerns with Mobile Loan Apps in Kenya - Munyendo, Collins W.; Acar, Yasemin; Aviv, Adam J. (43rd IEEE Symposium on Security and Privacy, SP 2022, San Francisco, CA, USA, May 22-26, 2022)

Committed by Accident: Studying Prevention and Remediation Strategies Against Secret Leakage in Source Code Repositories - Krause, Alexander; Klemmer, Jan H.; Huaman, Nicolas; Wermke, Dominik; Acar, Yasemin; Fahl, Sascha (CoRR)

KI im Einsatz. Interdisziplinäre Herausforderungen im Projekt UAV-Rescue - Philippi, Martina; Heusinger-Heß, Victoria; Ari, Meral; Krüger, Emily (Mensch und Computer 2022 - Workshopband)
Im Projekt „UAV-Rescue: UAV-getragene Sensorik zur KI-basierten Unterstützung von Rettungsmissionen“ wird an einem unbemannt fliegenden System geforscht, das in schwer zugänglichen Räumen bei der Rettungspriorisierung hilft, indem es den Einsatzkräften eine Visualisierung des Raumes mit darin lokalisierten Lebenszeichen zur Verfügung stellt. Diese neue Technologie wirft verschiedene ethische Fragestellungen auf, die unter anderem die Nutzung von Künstlicher Intelligenz zur Lebenszeichendetektion und die Einbettung der neuen Technologie in die Einsatzpraxis betreffen. Die ethische Begleitforschung des Projekts adressiert diese Fragestellungen in einem interdisziplinären und iterativen Diskurs mit Technikpartnern und Endanwendern. Einige dieser Fragestellungen werden hier vor dem Hintergrund der eingesetzten KI-Methoden und der bestehenden Einsatzpraxis beim THW vorgestellt.
Keywords: rescue robotics; interdisciplinarity; artifical intelligence; ethics

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure

Betriebliche Gesundheitsförderung: Ein leeres Versprechen? - Auer, Thorsten Fabian; Sennefelder, Lisa; Meier, Heiko (Public Health Forum)
Unternehmen investieren zunehmend in Angebote Betrieblicher Gesundheitsförderung (BGF). Dabei stellt sich die Frage nach dem Kosten-Nutzen-Verhältnis jenseits des individuellen Nutzens durch die Förderung der Mitarbeitergesundheit. Deshalb wurden im Rahmen einer Sekundäranalyse Effekte der BGF auf den Unternehmenserfolg berechnet. Die Ergebnisse lassen vermuten, dass sich eine verhaltensorientierte BGF kaum positiv auf die Arbeitsproduktivität und Kommunikationsstruktur in Unternehmen auswirkt.
Keywords: Kommunikation; Arbeitsproduktivität; Betriebliche Gesundheitsförderung; Kosten-Nutzen-Verhältnis

Themes from the Philosophy of Robert Brandom - Bloch-Mullins, Corinne; Choi, Yoon H.; Luft, Sebastian (Journal of Transcendental Philosophy)
Keywords: General Medicine

Rezension zu Heinrich Wilhelm Schäfer, Die Taufe des Leviathan. Protestantische Eliten und Politik in den USA und Lateinamerika, Bielefeld 2021 - Pinsch, Jan Christian (Paderborner Historische Mitteilungen)

"Nichts über uns ohne uns". Wie Wissenstransfer inklusiv und partizipatorisch gestaltet werden kannWissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher ForschungWissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung - Neumann, Anna (Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung)

Kannst du dieses Mal meine Stimme hören? Von unerfüllten und unerfüllbaren Träumen, Gottesklage und Ableismus - Neumann, Anna (Praxis Inklusion. Religionspädagogische Fachzeitschrift: Träume)

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Entrepreneurship, Green Business - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Creative Thinking - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Canvas Model - Schneider, Jennifer Nicole

EU-CERT. First Transnational Project Meeting. Presentation at the EU-CERT Meeting: Financial, Marketing and Dissemination. - Schneider, Jennifer Nicole

Family Business Library. Presentation at the LTTA of FBL: Motivation, Barriers and Problems while starting a business - Schneider, Jennifer Nicole

Nutzung von Process Mining in RPA-Projekten - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Praxishandbuch Robotic Process Automation (RPA))

Adapting the product design to the circular economy using R-principles - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Report on the E-TEMS 2022 Doctoral Workshop “Smart Cities as System of Systems” - Kaiser, Lydia; Kapp, Alexandra; Wardzinska, Katarzyna; Hegyi, Dora; Kobler, Corinna; Venegas, Jaime; Schrader, Elena; Tissen, Denis; Mundt, Enrik (2022 IEEE European Technology and Engineering Management Summit (E-TEMS))

Influence of Processing Glass-Fiber Filled Plastics on Different Twin-Screw Extruders and Varying Screw Designs on Fiber Length and Particle Distribution - Rüppel, Annette; Wolff, Susanne; Oldemeier, Jan Philipp; Schöppner, Volker; Heim, Hans-Peter (Polymers)
Due to their valuable properties (low weight, and good thermal and mechanical properties), glass fiber reinforced thermoplastics are becoming increasingly important. Fiber-reinforced thermoplastics are mainly manufactured by injection molding and extrusion, whereby the extrusion compounding process is primarily used to produce fiber-filled granulates. Reproducible production of high-quality components requires a granulate in which the fiber length is even and high. However, the extrusion process leads to the fact that fiber breakages can occur during processing. To enable a significant quality enhancement, experimentally validated modeling is required. In this study, short glass fiber reinforced thermoplastics (polypropylene) were produced on two different twin-screw extruders. Therefore, the machine-specific process behavior is of major interest regarding its influence. First, the fiber length change after processing was determined by experimental investigations and then simulated with the SIGMA simulation software. By comparing the simulation and experimental tests, important insights could be gained and the effects on fiber lengths could be determined in advance. The resulting fiber lengths and distributions were different, not only for different screw configurations (SC), but also for the same screw configurations on different twin-screw extruders. This may have been due to manufacturer-specific tolerances.
Keywords: Polymers and Plastics; General Chemistry

Identification of Human and Organizational Key Design Factors for Digital Maturity – A Fuzzy-Set Qualitative Comparative Analysis - Schneider, Martin; Hellweg, Talea Davina; Menzefricke, J. S. (Proceedings of the Design Society)
Abstract This paper examines how human and organizational factors need to be designed to achieve strong technological maturity of either the products or the production process. In a fuzzy-set qualitative comparative analysis (fs/QCA), a combination of intensive training and strong worker participation is found to be associated with strong technological maturity in the two organizational contexts: firms with a strong entrepreneurial culture and in large firms oriented towards customer-oriented innovation. Overall, the paper uncovers designs or causal recipes for a successful digital transformation.

Erst Überfluss, dann überflüssig? Erneuerungsdialoge zwischen Unternehmensgeschichte und (allgemeiner) Geschichtswissenschaft - Staffel, Florian Lukas